2014
DOI: 10.11604/pamj.2014.17.168.2453
|View full text |Cite
|
Sign up to set email alerts
|

Forestier’s disease presenting with dysphagia and disphonia

Abstract: Forestier's disease, also known as diffuse idiopathic skeletal hyperostosis (DISH), is a pathology of vertebral bodies characterised by exuberant osteophytis formation. Forestier's disease is usually managed conservatively. Surgical resection of the osteophytes is reported to be an effective treatment for severe cases and/ or cases with airway obstruction. We report a 55-year-old man presenting with 6 months’ progressive dysphagia and dysphonia. He was managed successfully with an anterior cervical osteophytec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Forestier disease is defi ned as a non-infl ammatory ossifi cation of spinal and peripheral elements [5,6] and was fi rst reported by Forestier and Rotes-Querol in 1950 [5] and later named as DISH by Resnick, et al, in 1975 [7]. Three criteria for diagnosis is crucial for this condition: ossifi cation of the anterior longitudinal ligament in at least four vertebral bodies successively, preservation of intervertebral disc height and intra-articular osseous fusion or sclerosis with absence of apophyseal joint bone ankylosis and sacroiliac joint erosion [5,8]. It is mostly seen in the thoracic region [5,9], but cases of the other vertebra segments are reported as well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Forestier disease is defi ned as a non-infl ammatory ossifi cation of spinal and peripheral elements [5,6] and was fi rst reported by Forestier and Rotes-Querol in 1950 [5] and later named as DISH by Resnick, et al, in 1975 [7]. Three criteria for diagnosis is crucial for this condition: ossifi cation of the anterior longitudinal ligament in at least four vertebral bodies successively, preservation of intervertebral disc height and intra-articular osseous fusion or sclerosis with absence of apophyseal joint bone ankylosis and sacroiliac joint erosion [5,8]. It is mostly seen in the thoracic region [5,9], but cases of the other vertebra segments are reported as well.…”
Section: Discussionmentioning
confidence: 99%
“…Three criteria for diagnosis is crucial for this condition: ossifi cation of the anterior longitudinal ligament in at least four vertebral bodies successively, preservation of intervertebral disc height and intra-articular osseous fusion or sclerosis with absence of apophyseal joint bone ankylosis and sacroiliac joint erosion [5,8]. It is mostly seen in the thoracic region [5,9], but cases of the other vertebra segments are reported as well. In the cervical region it is mostly seen in the subaxial segment between C4-C7 [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have reported that surgery is effective in cases of DISH if dysphagia is serious or if conservative therapy has proven ineffective. 16 , 18 22) Conversely, some other studies have found that aspiration pneumonia may occur after removal of the osteophytes, implying that surgery is not effective 23) Therefore, as yet, there is no unified consensus. In the present case, the patient improved from FILS Level 2 to Level 7 as a result of conservative intervention with dysphagia rehabilitation, and became capable of eating semi-solid food by means of postural adjustment.…”
Section: Discussionmentioning
confidence: 99%